O.3.1Exploring general practice patient needs and expectations of online access to their medical records: Presenter(s): Ciska Hoving, Maastricht University, Netherlands. (April 2023) - Thielmann, Rosa; Schutgens-Kok, Esther; Cals, Jochen; Crutzen, Rik
Abstract : Background: Patient online access to medical records is assumed to foster patient empowerment and advance patient-centered healthcare. Since July 2020, patients in the Netherlands are legally entitled to electronically access their medical record from their general practice. However, findings from pioneering countries shows that despite high patient interest, actual user rates often remain low. How to best support implementation highly depends on patients' needs and expectations, which are yet unknown in the Dutch context. Therefore, the aim of this study was to identify those needs and expectations regarding online access to medical record in general practice. Method: Twenty participants completed semi-structured individual interviews via video or telephone call. Transcripts of interviews underwent template analysis combining deductive and inductive coding using Atlas.ti software. Results: Patients' needs and expectations ranged across three overlapping areas: 1) prerequisites for gaining online access, 2) using online access, and 3) the impact of access on interaction with healthcare providers. Patients expected benefits from online access such as better overview, personal empowerment, and improved communication with their general practitioner, but expressed concern about technological difficulties, complicated medical language, and data privacy. Discussion: The benefits participants expected underline high patient interest in online access to medical records. The concerns and obstacles participants identified point towards the need for organisational changes in general practice (e.g., regarding documentation practices), and the key role of the provider and staff in promoting and facilitating online access. Implementation strategies addressing needs identified in this study can help to unlock the full potential of online access to achieve desired outcomes of patient involvement and satisfaction.